Pengaruh Metode Pembelajaran Story Telling Terhadap Perkembangan Emosional Anak - Widiya Kristiana; Naili Sa’ida; Wahono; Tri Kurniawati (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2026)
Emotional development is a crucial aspect of early childhood development that influences children’s social abilities and readiness to engage in learning environments. One instructional approach that can be used to stimulate children’s emotional development is storytelling. This study aimed to examine the effect of the storytelling activity “Mimo and Kiko” on the emotional development of children aged 5–6 years at TK Islam Insan Mulia Mojokerto. The study employed a quantitative approach using a quasi-experimental design with a pretest–posttest model. The participants consisted of 39 children aged 5–6 years. Data were collected through systematic observation using an instrument based on three aspects of emotional development: emotional understanding, emotional expression, and emotional regulation. The instrument underwent content validity testing and demonstrated good reliability, with a Cronbach’s Alpha value of 0.82. The results indicate that the storytelling activity “Mimo and Kiko” had a positive effect on children’s emotional development, particularly in the aspects of emotional understanding and emotional expression, while emotional regulation developed more gradually. These findings suggest that storytelling can serve as an effective instructional strategy for stimulating emotional development in early childhood education settings.